Career Development Strategies to Improve Human Resources Sustainability in Organisations - Muhammad Ikram Idrus; Muhammad Ihsan Said Ahmad; Muhammad Ishlah Idrus (Student Research Journal, 2023)
In the era of globalisation and increasingly fierce competition, the sustainability of human resources (HR) becomes very important for the success of the organisation. Organisations that have effective career development strategies are able to retain quality human resources, increase productivity, and create a competitive advantage. The purpose of this study is to identify and analyse effective career development strategies in improving HR sustainability in organisations. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that in the context of improving HR sustainability in organisations, career development strategies play a very important role. In the above, we have discussed effective and relevant career development strategies by accommodating individual personality preferences and ensuring a match between the individual, the work environment, and organisational values. Holland's Career Choice Theory provides valuable insights in designing sustainable career development strategies.